Pengaruh Perilaku Belajar dan Penggunaan Google Classroom terhadap Hasil Belajar Mata Kuliah Entrepreneur 1 pada Mahasiswa Universitas Bhinneka PGRI - Tanammal, Ahmad Yunan Bured; Hairunisya, Nanis (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of learning behavior and the use of google classroom on the learning outcomes of the Entrepreneur 1 course for Bhinneka PGRI University students. This study uses a quantitative technique with a survey method with a population of 135 students, the researcher uses the Slovin formula with an error limit of 0.1 and the number of samples obtained is 58 students. The data analysis used is the research instrument test: validity test and reliability test, classical assumption test: normality test, linearity test, multicollinearity test and heteroscedasticity test, regression analysis: multiple linear regression analysis and coefficient of determination and hypothesis test: t test (test partial) and F test (simultaneous test) using the SPSS version 21 program. Based on the results of the study, the analysis of the coefficient of determination shows that the variables of learning behavior and the use of google classroom affect learning outcomes by 53.9%. And it was found that the variables of learning behavior and the use of google classroom partially have a significant relationship to learning outcomes. In addition, the variables of learning behavior and the use of google classroom simultaneously have a significant effect on learning outcomes.